Improving of Literacy Movement for Pimpinan Daerah Nasyiatul ‘Aisyiyah Kota Yogyakarta and Pimpinan Cabang Ikatan Mahasiswa Muhammadiyah AR Fakhruddin Kota Yogyakarta - Tanto Lailam; Ani Yunita; Nita Andrianti; M. Ulul Albab Asas (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The literacy movement focuses on improving critical thinking skills for young cadres. The partners in this community service are the Department of Education the Pimpinan Daerah Nasyiatul ‘Aisyiyah Kota Yogyakarta and Branch Leaders of the Ikatan Mahasiswa Muhammadiyah AR Fakhruddin Kota Yogyakarta. This program begins with various literacy studies and literacy understanding, including e-literacy and literacy movement, literacy 4.0, political literacy. Activities related to critical thinking, namely writing